Maternal prediabetes as a risk factor of preeclampsia and placental dysfunction in pregnant female Sprague-Dawley rats - Aneliswe Siboto; Asiphaphola Ludidi; Ntethelelo Sibiya; Andile Khathi; Phikelelani Ngubane (Taylor & Francis Group, 2024)
Background Prediabetes (PD) is associated with intermediate hyperglycaemia, dyslipidaemia, reduced nitric oxide (NO) bioavailability and moderate hypertension. All these factors are risk factor for preeclampsia (PE). However, the effects of the PD on placental function have not been shown. Accordingly, this study sought to investigate a possible link between maternal PD and the risk of developing PE.Methods Pregnant female Sprague-Dawley rats (N = 18) were divided into normal, preeclamptic and prediabetic groups (n = 6 in each group) to study the effects of maternal PD on placenta function over the period of 19 days. Blood glucose and blood pressure were measured on gestational day (GND) 0, 9 and 18. Placental vascular endothelial growth factor (VEGF), placenta growth factor (PlGF) and soluble fms-like tyrosine kinase 1 (sFlt-1) mRNA expression were measured terminally. Data were analysed using ANOVA followed by the Tukey-Kramer post hoc test. Values of p < .05 were used to indicate statistical significance.Results Maternal PD and PE significantly increased blood glucose, decrease NO concentration and increase in MAP by comparison to the normal pregnant control group. Maternal PD significantly decreased VEGF, PlGF mRNA expression with a slight increase in sFlt-1 mRNA expression comparison to the normal pregnant control group.Conclusions Maternal PD is associated with placental dysfunction due to impaired glucose handling, endothelial dysfunction and an imbalance in angiogenic and antiangiogenic factors. Therefore, maternal PD is a risk factor of PE.